A study of biochemical parameters and microbial organisms in ascitic fluid of spontaneous bacterial peritonitis patients - Rahul Gadekar; Arun Tyagi; Marcia Waran; A.K. Srivastava (International Journal of Medical Research and Review, 2018)
Introduction:Spontaneous Bacterial Peritonitis (SBP) is recognized as a severe complication in patients of ascites. In recent years, it has also been diagnosed in patients without liver disease. SBP is commonly reported in patients of ascites due to cirrhosis of liver. If untreated, SBP could be a fatal complication in patients of ascites.Objective:To study the ascitic fluid biochemical parameters and causative micro-organisms in patients suffering from SBP.Materials and Methods:A prospective study was performed on 100 patients of ascites out of which 68 were males and 32 were females. After admission all patients were interviewed and detailed history and complete physical examination was performed.Results:In this study 86.7% patients had increased serum bilirubin levels, 73.4% patients had decreased serum albumin, 46.7% and 40% patients had increased blood levels of urea and creatinine respectively. 60% patients had ascitic fluid pH < 7.30 while 80% patients had ascitic fluid proteins < 1 gm/dl. All patients had >250 polymorphonuclear cells/µL and 80% patients had >500 polymorphonuclear cells/ µL in ascitic fluid. 46.7% cases of SBP were culture positive and 53.3% were culture negative.Gram staining of ascitic fluid was positive in one case.Conclusion:Hypoalbuminemia, hyperbilirubinemia, low ascitic fluid pH, low ascitic fluid proteins, increased blood urea and creatinine levels are risk factors related with development of SBP in patients of ascites.The commonest micro-organism identified on culture were E-coli.